Extending the handprint approach for the assessment of circular solutions to study the potential positive climate impacts of workplace-as-a-service system - Mikko Ropo; Kaisa Grönman; Laura Lakanen; Katri Behm; Risto Soukka (Cleaner Engineering and Technology)
Circular economy is identified as a fundamental socio-technological systemic solution to solve the over-arching sustainability challenges resulting from human action, which entails an urgent need to implement circular economy solutions. To identify sustainable solution alternatives, a deeper understanding of impacts on the environmental sustainability of systems is needed. The goal of this study is to extend and apply the handprint approach to the assessment of potential positive environmental impacts of circular solutions. The extended handprint framework is tested in a case study to find out the potential positive climate impacts of a workplace-as-a-service system, which utilises several circularity strategies to lower the climate impact of office spaces in a system of several customers. In the simulated case study for three different customers, the workplace-as-a-service solution was found to decrease the life cycle greenhouse gas emissions of the studied system by 50% compared to a baseline of a business-as-usual office space during a time-period of 30 years. The handprint approach was found to be applicable to the assessment of positive environmental impacts in the studied case, while being compatible with existing methods and standards.